The Pseudomonas syringae pv. tomato HrpW protein has domains similar to harpins and pectate lyases and can elicit the plant hypersensitive response and bind to pectate. - Charkowski, A; Alfano, JR; Preston, G; Yuan, J; He, S; Collmer, A (1998)
The host-specific plant pathogen Pseudomonas syringae elicits the hypersensitive response (HR) in nonhost plants and secretes the HrpZ harpin in culture via the Hrp (type III) secretion system. Previous genetic evidence suggested the existence of another harpin gene in the P. syringae genome. hrpW was found in a region adjacent to the hrp cluster in P. syringae pv. tomato DC3000. hrpW encodes a 42. 9-kDa protein with domains resembling harpins and pectate lyases (Pels), respectively. HrpW has key properties of harpins. It is heat stable and glycine rich, lacks cysteine, is secreted by the Hrp system, and is able to elicit the HR when infiltrated into tobacco leaf tissue. The harpin domain (amino acids 1 to 186) has six glycine-rich repeats of a repeated sequence found in HrpZ, and a purified HrpW harpin domain fragment possessed HR elicitor activity. In contrast, the HrpW Pel domain (amino acids 187 to 425) is similar to Pels from Nectria haematococca, Erwinia carotovora, Erwinia chrysanthemi, and Bacillus subtilis, and a purified Pel domain fragment did not elicit the HR. Neither this fragment nor the full-length HrpW showed Pel activity in A230 assays under a variety of reaction conditions, but the Pel fragment bound to calcium pectate, a major constituent of the plant cell wall. The DNA sequence of the P. syringae pv. syringae B728a hrpW was also determined. The Pel domains of the two predicted HrpW proteins were 85% identical, whereas the harpin domains were only 53% identical. Sequences hybridizing at high stringency with the P. syringae pv. tomato hrpW were found in other P. syringae pathovars, Pseudomonas viridiflava, Ralstonia (Pseudomonas) solanacearum, and Xanthomonas campestris. DeltahrpZ::nptII or hrpW::OmegaSpr P. syringae pv. tomato mutants were little reduced in HR elicitation activity in tobacco, whereas this activity was significantly reduced in a hrpZ hrpW double mutant. These features of hrpW and its product suggest that P. syringae produces multiple harpins and that the target of these proteins is in the plant cell wall.